"My parents are pretty pleased with my maths": students' navigation of identity stories about mathematics. Issue 1 (2nd January 2022) - Ingram, Naomi; Meaney, Tamsin
ABSTRACT: Although it is assumed that parents influence their children's lives, little is known about how students navigate between their own expectations and their parents' views of mathematics and how this navigation affects mathematical learning. Using an exemplary case of Philip, we illustrate how he made sense of his father's high expectations related to his engagement with mathematics. There were three tensions evident in Philip's stories about mathematics related to these expectations: the utility of mathematics for his future career; his expectations of doing well in mathematics; and the value of mathematics teachers. The results, elaborated on by the perspectives of the other students in Philip's Year 10 class, shed light on the complexity and fluidity of secondary school students' identities, in relationship to their mathematical engagement.